2012
DOI: 10.4143/crt.2012.44.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Metachronous Double Primary Cancer after Diagnosis of Gastric Cancer

Abstract: PurposeThe pattern of double primary cancers after treatment for gastric cancer is important for a patient's survival.Materials and MethodsWe analyzed the clinicopathologic data of 214 gastric cancer patients from October 1996 to November 2007 with regard to metachronous second primary cancers.ResultsOut of 5,778 patients with gastric cancer, metachronous second primary cancers occurred in 214 patients. The median age was 61.8 years, the number of male and female patients was 140 (65.4%), 74 (34.6%), respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 12 publications
2
25
0
Order By: Relevance
“…In the present study, of the 3066 GC patients who underwent curative gastrectomy, 70 patients (2.3%) had been diagnosed with a metachronous or synchronous MPC, which is consistent with results of previous reports that reported a range from 2.0 to 7.6% [7-9,11,23]. Few previous studies have reported the incidence and clinical pattern of MPC in GC patients who underwent curative gastrectomy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, of the 3066 GC patients who underwent curative gastrectomy, 70 patients (2.3%) had been diagnosed with a metachronous or synchronous MPC, which is consistent with results of previous reports that reported a range from 2.0 to 7.6% [7-9,11,23]. Few previous studies have reported the incidence and clinical pattern of MPC in GC patients who underwent curative gastrectomy.…”
Section: Discussionsupporting
confidence: 92%
“…If we extend the duration of follow-up in future study, it will better characterize the predictive factors of MPCs. To date, there are several reports regarding the development of MPCs in GC survivors [7-9,23]. However, these are not sufficient to justify the routine screening for the detection of MPC in all GC survivors; it is also difficult to address the optimal screening protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of metachronous SPCs after the diagnosis of gastric cancer has been estimated in previous studies: in Korea, patients who underwent curative resection of gastric cancer were retrospectively reviewed showing a 5-year cumulative incidence of SPC of 1.4% [27], and in Japan, the occurrence of second tumours at least six months following resection of early gastric cancer was estimated at 5.0% after more than 10 years of follow-up [28]. Another study, from Korea, had an incidence of 3.7% with a median time to the occurrence of metachronous SPC six months or more after diagnosis of the gastric FPC of 3.3 years (standard deviation: 2.6 years) [29]. Our overall cumulative incidence of metachronous SPCs more than two months after the FPC was 3.1 and 4.8% at 5-and 10-years, respectively; corresponding estimates using a six month cut-off to define SPCs were 3.3 and 5.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of reasons for the increased survival of gastric cancer patients, for instance more hygienic strategies for food conservation, increased screening using upper gastrointestinal panendoscopy, better surgical techniques, improved lymph node dissection, and advances in adjuvant chemotherapy and radiotherapy [6]. However, the risk of second primary malignancy (SPM) is of concern because patients with SPMs present lower survival rates than those without [7][8][9]. Several single institutes in Asia have reported that SPMs occur in gastric cancer patients at incidences of 0.9-3.4 % [9][10][11].…”
Section: Introductionmentioning
confidence: 99%